Changes in global, domestic, and stock price as a response to Indonesian CPO export ban: An opening door into a worldwide financial distress - Hadi Wibowo; Helmi Adam; Mega Fauziah (International Journal of Science and Society, 2023)
In April 2022, Indonesian government decided to implement a policy to ban crude palm oil (CPO) exports due to the scarcity of cooking oil in domestic market, which was revoked after twenty-one days put into effect. Considering the important contribution of CPO trade particularly to food and consumer goods industries, a sudden cessation of CPO supplies might instigate financial distress across the globe. This research aims to measure changes in global and domestic CPO price as well as stock price of IDX-listed CPO companies in response to the enactment of CPO export ban under the Decree 22/2022. At the first stage, a descriptive measurement is employed to analyze the monthly changes in value for each price variable. At the second stage, the Pearson's correlation coefficient is applied to measure the statistical relationship between two price variables. The result shows that the domestic market responded more quickly with a 16.77% price drop in May 2022 while global price increased slightly by 2.03% due to the shortage of CPO supply. Nonetheless, a sharp decline in global price of 12.57% occurred in June 2021 shortly after the export ban policy lifted. A moderately strong correlation is found between domestic and global price, expressing a quite similar fluctuation trends for both. In relation to the stock price, neither global price nor domestic price is significantly correlated with. Notwithstanding, both variables are not significantly correlated with the stock price. Stock price shows a rapid return when the CPO trading reopened. This research may contribute to the development of science in economic and financial risk as well as to the government in making future CPO trade policies. As a relatively new issue, there is no similar scientific study to this research found which can be counted a novelty.